Transição para negócios digitais: uma análise das rotinas dinâmicas em agências bancárias - Hamerschmidt, Marisa Biehl (2020)
The emergence and improvement of ICTs - Information and Communication Technologies - led to a transformation in the way of life of great proportions, both in people's habits and in the production processes. In the business environment, innovation has become a determining factor in the generation of wealth, and in the Brazilian banking sector it has triggered an increase in competition for multiple banks, with the emergence of digital banks, fintechs and credit unions. In such a context, institutional reorganizations and reconfigurations of the business model occur. Thus, this research investigated this scenario in a Brazilian banking institution, which was called Banco $, in light of the constructs of the business model, routines and dynamic capabilities in the organizational strategy. The general objective of the investigation was to analyze the organizational routines present in the face-to-face service of bank branch customers $, from the introduction of digital processes in the business model. The specific objectives sought to contextualize the striking aspects of the digital transition and the adoption of the new business model at Banco $, to identify the ostensive and performative elements of the routines related to face-to-face service and to point out innovative solutions for improving processes based on capacities. dynamics of the organization. For that, the qualitative method was used, adopting the interpretative perspective and carrying out a case study, with an exploratory character and a longitudinal approach (2016-2019). Data collection took place through semistructured interviews and documentary data, and triangulation between such primary and secondary sources was carried out in conjunction with the literature used. The survey revealed that many organizational routines were reconfigured as the new business model and organizational change deepened. Such routines manifest in their ostensible aspect the predominance of business practice as a goal for generating revenue and in the performative aspect the interdependence of other routines, as well as the agency (ability to act) by employees. As for the dynamic capabilities of Banco $, its generating potential was evidenced through the materialization of several reorganizations of the company, in the form of rearrangements of physical and human resources in the period surveyed.